2021
DOI: 10.1016/j.jgo.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Omission of adjuvant radiotherapy for older adults with early-stage breast cancer particularly in the COVID era: A literature review (on the behalf of Italian Association of Radiotherapy and Clinical Oncology)

Abstract: This review is aimed at evaluating whether radiation therapy (RT) can be omitted in older adult early-stage lowrisk breast cancer (BC) patients. The published data are particularly relevant at present, during the COVID-19 pandemic emergency, to define a treatment strategy and to prioritize essential therapy. Cochrane Database of Systematic Reviews and PubMED were systematically researched from outset through April 2020 using Mesh terms. Only randomized controlled trials (RCT), with one arm without adjuvant who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…HFRT should be the standard of care. Partial breast irradiation and ultra- HFRT regimens could be considered in selected cases due to the pandemic [ 117 , 119 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HFRT should be the standard of care. Partial breast irradiation and ultra- HFRT regimens could be considered in selected cases due to the pandemic [ 117 , 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvant RT might be omitted in a highly selected group of older adult early-stage breast cancer patients with favorable prognostic factors [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, the actively evolving scientific understanding of breast cancer biology is driving clinical trials that are providing radiation oncologists and women with breast cancer with the information they need to make personalized choices that both protect them from recurrences and from unwarranted treatment morbidity. In view of the evolving evidence, therapeutic strategies incorporating tumor and patient characteristics, as well as patient preferences, should be discussed in a multidisciplinary tumor board to tailor the treatment for the patient [10].…”
Section: Discussionmentioning
confidence: 99%
“…This need has prompted re-consideration of radiotherapy indications and has initiated investigations to identify any subset of low-risk women with such a negligible burden of residual locoregional disease risk following breast-conserving surgery who could be safely spared radiation therapy. In particular, much attention has been focused lately on elderly early-stage breast cancer patients with favorable prognostic factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors found no association between anticancer treatment and COVID-19, noting that adverse COVID-19 outcomes and increased mortality were associated with older adults with cancer regardless of their treatment status. Possible omission of radiotherapy was suggested by Palumbo et al [20] in select older adults with early-stage breast cancer. These authors also suggest that given the high risk for older adults with cancer, risk and benefit must be carefully weighed and suggest that delay or reduction in visits to healthcare centres may be a reasonable approach.…”
Section: Overview Of Reviewsmentioning
confidence: 97%